2022
DOI: 10.1111/joss.12740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of product properties and context on the perception of sweetness and liking: A case study with butter cookies

Abstract: Consumption context has been shown to significantly contribute to food acceptance, probably because of affecting food attributes' perception. The present study investigated the influence of multisensory reformulation on the acceptance and perceived sweetness of butter cookies in two contexts (Central Location Test, CLT vs. Home Use Test, HUT). The objective was to determine whether the use of some natural aromas could trigger a sweet‐taste‐like emotional response in a confectionery product, and if consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It is possible that the explicit response collected in the sensory lab was different from the one recorded in the restaurant because the real context experiment included the effect of the whole drinking experience, and therefore provided a more realistic consumer response to the products. On the contrary, the controlled context may have contributed to focusing on the differences among samples' flavor, similarly as reported by Romeo-Arroyo,Mora, Pazos, Deba-Rementeria, and Vázquez-Araújo (2022) in a study conducted on cookies samples assessed in a controlled context and using a Home-Use-Test approach. Despite the limited information offered by the implicit data, using a real context approach was suitable to collect the signals and product differentiation was possible with the proper data process and analysis, opening possibilities to further research in real context using implicit response technologies.…”
mentioning
confidence: 53%
“…It is possible that the explicit response collected in the sensory lab was different from the one recorded in the restaurant because the real context experiment included the effect of the whole drinking experience, and therefore provided a more realistic consumer response to the products. On the contrary, the controlled context may have contributed to focusing on the differences among samples' flavor, similarly as reported by Romeo-Arroyo,Mora, Pazos, Deba-Rementeria, and Vázquez-Araújo (2022) in a study conducted on cookies samples assessed in a controlled context and using a Home-Use-Test approach. Despite the limited information offered by the implicit data, using a real context approach was suitable to collect the signals and product differentiation was possible with the proper data process and analysis, opening possibilities to further research in real context using implicit response technologies.…”
mentioning
confidence: 53%
“…Even though MintC and GreenT were rated less sweet than the rest of the samples, when combined with non-congruent teas/cookies, sweetness was slightly enhanced ( Table 5 ). Previous research has shown that vanilla could be used to enhance the perception of sweetness in cookies ( Romeo-Arroyo et al, 2022 ). It is known that olfactory stimuli that have regularly been paired with sweet-tasting foods (e.g., vanilla, strawberry) could enhance the associated taste quality ( Spence, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aroma has been shown to be a potential sweetness enhancer in several studies (Bertelsen et al, 2021;Boakes & Hemberger, 2012;Proserpio et al, 2021;Wang et al, 2019). Previous research has shown that a 40% reduction in the sugar content of a cookie sample did not affect overall liking when adding vanilla aroma in both controlled and real home-use-test contexts (Romeo-Arroyo et al, 2022). Also, Danish and Chinese consumers rated different sweeteners samples with added vanilla aroma higher in sweet taste intensity than samples without added aroma, although some differences were found between consumers' ratings (Bertelsen et al, 2021).…”
Section: Crossmodal Assessmentmentioning
confidence: 97%